Dilamba': Dilamba’ Heutagogical Guided Freedom in Toraja Culture for Fostering Child Autonomy and Moral Development - Rannu Sanderan; Piter Randan Bua (PEADA': Jurnal Pendidikan Kristen, 2026)
Dilamba’, a child-rearing practice rooted in Toraja culture, embodies guided freedom that balances autonomy with parental and community support. This study investigates how Dilamba’ fosters independence, decision-making, creativity, and moral growth by integrating indigenous wisdom with heutagogical principles. Using a qualitative, conceptual-cultural approach, the research combined literature review, field observations, and interviews to examine child behavior, parenting practices, and communal involvement. Results indicate that Dilamba’ encourages exploratory behavior, problem-solving, resilience, and ethical awareness, while active engagement from parents and the community is pivotal for nurturing autonomy. Children participating in this model evolved from dependency to competence, displaying maturity, moral reasoning, and self-directed decision-making. The integration of traditional practices with contemporary pedagogical insights, including Montessori, Froebel, and Mangunwijaya, presents a holistic educational framework. Dilamba’ thus offers a culturally grounded approach to raising self-directed, morally conscious, and capable children, providing guidance for curriculum development, parenting programs, and educational interventions bridging tradition with modern learning paradigms.